2000
DOI: 10.1523/jneurosci.20-01-00089.2000
|View full text |Cite
|
Sign up to set email alerts
|

Control of GluR1 AMPA Receptor Function by cAMP-Dependent Protein Kinase

Abstract: Modulation of postsynaptic AMPA receptors in the brain by phosphorylation may play a role in the expression of synaptic plasticity at central excitatory synapses. It is known from biochemical studies that GluR1 AMPA receptor subunits can be phosphorylated within their C terminal by cAMP-dependent protein kinase A (PKA), which is colocalized with the phosphatase calcineurin (i.e., phosphatase 2B). We have examined the effect of PKA and calcineurin on the time course, peak open probability (P O,PEAK ), and singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
512
1
9

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(542 citation statements)
references
References 82 publications
20
512
1
9
Order By: Relevance
“…Interestingly, in addition to protecting the AMPA receptor GluA1 subunit, the equipotent endocannabinoid modulator protected the ability of GluA1 to be phosphorylated by cAMP-dependent protein kinase at residue serine-845, moreso than the AM6702 treatment. This posttranslational modification of AMPA channels has been found to increase their open probability [59], to regulate their cell surface expression [60], and to promote long-term potentiation and retention of spatial memory [61,62]. KA-induced disruption of the GluA1 phosphorylated state may contribute to the seizure-mediated decline in brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to protecting the AMPA receptor GluA1 subunit, the equipotent endocannabinoid modulator protected the ability of GluA1 to be phosphorylated by cAMP-dependent protein kinase at residue serine-845, moreso than the AM6702 treatment. This posttranslational modification of AMPA channels has been found to increase their open probability [59], to regulate their cell surface expression [60], and to promote long-term potentiation and retention of spatial memory [61,62]. KA-induced disruption of the GluA1 phosphorylated state may contribute to the seizure-mediated decline in brain function.…”
Section: Discussionmentioning
confidence: 99%
“…In general, increased phosphorylation leads to LTP and decreased phosphorylation leads to LTD 129,130 . CaMKII and PKC can phosphorylate the GluA1 subunit at S831 131 , which increases the conductance of homomeric GluA1 and GluA1/2 heteromers in the presence of TARPs 132 , while PKA phosphorylates GluA1 at S845, increasing the peak conductance and open probability of the channel 133 . Knock-in mice expressing GluA1 or GluA2 subunits mutated to non-phosphorylatable or phosphomimetic residues have demonstrated that phosphorylation of GluA1 by CaMKII or PKA is necessary for full hippocampal LTP expression 134 , while dephosphorylation of the PKA site in GluA1 is required for LTD 46 .…”
Section: Ampar Phosphorylationmentioning
confidence: 99%
“…AKAP-bound PKA enhances the phosphorylation of Ser 845 in the cytoplasmic tail of GluR1 and is believed to stabilize AMPA currents 11,12 . Conversely, the AKAP-bound phosphatase PP2B may mediate the rundown of GluR1 currents 13 (Fig.…”
Section: Functional Characterization Of Akap79-depleted Cellsmentioning
confidence: 99%
“…1d, black triangles). Importantly, downregulation of the GluR1 current was rescued following expression of the murine orthologue AKAP150 that is refractory to pSAKAP79i RNAi ( Signalling to AMPA channels requires anchored PP2B and SAP97 AKAP-bound PKA enhances the phosphorylation of Ser 845 in the cytoplasmic tail of GluR1 and is believed to stabilize AMPA currents 11,12 . Conversely, the AKAP-bound phosphatase PP2B may mediate the rundown of GluR1 currents 13 (Fig.…”
Section: Functional Characterization Of Akap79-depleted Cellsmentioning
confidence: 99%